Strategi Peningkatan Mutu Pendidikan Madrasah Melalui Studi Jurnal Tentang Manajemen Pendidikan - Hermila Sari Rambe; Suryatik (Jurnal Zeniusi, 2024)
This study is entitled "Strategies For Improving The Quality Of Education In Madrasah Through Journal Studies On Educational Management." This research formulates the problem of how educational management methods might enhance the quality of education in madrasahs. This research examines the significance of madrasahs in developing students' character and competencies, alongside the problems encountered in enhancing the quality of education inside these institutions. This research aims to find and analyse successful educational management strategies for implementation in madrasahs. The employed research method is a literature study utilising a descriptive-analytical methodology. Data is sourced from journals, research articles, and other pertinent documents addressing educational management in madrasahs. The chosen data analysis technique is qualitative analysis, focussing on the identification of significant themes and pertinent tactics. This research employs a theoretical framework comprising educational management theories, teacher professionalism development theories, and community engagement theories in education. The research findings suggest that advancing teacher professionalism, optimising resources, and augmenting school community involvement are essential ways for enhancing the quality of education in madrasahs. Effective educational administration can foster a supportive learning environment that facilitates the attainment of educational objectives. This discovery is anticipated to offer tangible benefits for madrasah administrators and education officials in developing and executing strategies that enhance the quality of education in madrasahs.